Gerontechnology Adoption in the Silver Market: Global Bibliometric Trends and Future Agenda - Jumbri, Isma Addi; Fauzan, Fauzan; Ismail, Albert Feisal @ Muhd Feisal; Utama, Iston Dwija; Kurnianingrum, Dian; Karmagatri, Mulyani; Atan, Nur Atika (International Review of Management and Marketing, 2026)
Malaysia is projected to become an aged nation by 2030, creating both opportunities and challenges for the expanding silver market. Gerontechnology integrates technology and gerontology to support the independence, health, and quality of life of older adults, yet its impact depends on acceptance as much as innovation. This study conducts a bibliometric and content analysis of global gerontechnology research to identify key drivers of technology acceptance and to position Malaysia within this emerging field. Publications indexed in Scopus were analysed using VOSviewer to map publication growth, collaboration networks, and thematic clusters. The results show a gradual shift from mainly health-oriented applications toward behavioural and marketing perspectives, emphasising determinants such as perceived usefulness, ease of use, trust, and affordability. Malaysia’s research contribution remains developing but demonstrates growing attention to digital health, assistive technologies, and active ageing solutions. Based on these insights, the study proposes a marketing-oriented research and innovation agenda for 2025 to 2035 that prioritises user-centred design, digital inclusion, and collaboration among industry, academia, and policymakers. Integrating consumer behaviour perspectives into gerontechnology development can accelerate adoption among older adults and strengthen Malaysia’s role in the regional silver economy.